2019
DOI: 10.1094/pdis-02-18-0374-re
|View full text |Cite
|
Sign up to set email alerts
|

Three Colletotrichum Species, Including a New Species, are Associated to Leaf Anthracnose of Rubber Tree in Hainan, China

Abstract: Colletotrichum gloeosporioides and C. acutatum have been reported to be causal agents of anthracnose disease of rubber tree. Recent investigations have shown that both C. gloeosporioides and C. acutatum are species complexes. The identities of Colletotrichum species causing anthracnose disease of rubber tree in Hainan, China, are unknown. In this study, 106 isolates obtained from rubber tree with symptoms of anthracnose were collected from 12 counties of Hainan and identified at the species complex level based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…It has been confirmed that C . siamense is the dominant species that causes anthracnose on these three crops in Hainan (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been confirmed that C . siamense is the dominant species that causes anthracnose on these three crops in Hainan (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plant‐pathogenic Colletotrichum species are often described as causing typical symptoms of anthracnose disease, including spots and sunken necrotic lesions on leaves, stems, flowers, and fruits, but they can cause other symptoms such as red rot on sugar cane, crown rot on strawberry and banana, and brown blotch on cowpea (Cannon et al, 2012). Anthracnose is an important disease of rubber tree, coffee, and areca palm in Hainan, resulting in significant yield losses (Cao et al, 2019a, 2019b, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gloeosporioides species complex that caused leaf anthracnose of rubber tree were C . siamense in Hainan (Cao et al ., ). In this study, 69.1% and 14.6% of isolates from coffee were identified to be these two species, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Colletotrichum siamense can infect more than 60 species of plants worldwide (Ji et al 2019), but there have been no previous reports of the pathogen on S. tonkinensis. In China, various diseases caused by C. siamense can infect other hosts include Sterculia nobilis (Zhang et al 2020a, b), Sterculia lanceolata (Zhang et al 2020a, b), Hevea brasiliensis (rubber tree) (Cao et al 2019), Mallotus oblongifolius (Partridge tea) (Liu et al 2018), Macadamia sp. (Qiu et al 2020), Litchi chinensis (Ling et al 2019), and Camellia sinensis (Wang et al 2016).…”
mentioning
confidence: 99%